Production, purification, and characterization of taxol and 10-DABIII from a new endophytic fungus gliocladium sp isolated from the Indian yew tree, taxus baccata - Sreekanth, D.; Syed, A.; Sarkar, S.; Sarkar, Dhiman; Santhakumari, B.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Microbiology and Biotechnology, 2009)
We have isolated endophytic fungi from the Indian yew tree, Taxus baccata, and then screened for taxol production. Out of the 40 fungal cultures screened, one fungus Gliocladium sp. was found to produce taxol and 10-DABIII (10-deacetyl baccatin III). These compounds were purified by TLC and HPLC and characterized using UV-spectroscopy, ESI-MS, MS/MS, and proton NMR. One liter of Gliocladium sp. culture yielded 10 mu g of taxol and 65 mu g of 10-DABIII. The purified taxol from the fungus showed cytotoxicity towards cancer lines HL-60 (leukemia), A431 (epidermal carcinoma), and MCF-7 (breast cancer).
Keywords: 10 DAB III; Endophytic fungi; Gliocladium sp.; Taxol; Taxus baccata

Influence of endophytic fungal elicitation on production of inophyllum in suspension cultures of Calophyllum inophyllum L. - Pawar, Kiran D.; Yadav, Amit V.; Shouche, Yogesh S.; Thengane, Shubhada Ratnakar (Plant Cell Tissue and Organ Culture, 2011)
The influence of dried cell powder and culture filtrates of endophytic fungi on production of inophyllum in cell suspension cultures of leaf- and stem-derived callus of Calophyllum inophyllum was investigated. Two fungi, Nigrospora sphaerica and Phoma spp., endophytic to C. inophyllum, were isolated from leaf tissues, and were identified by both 18S rRNA gene amplification and sequencing. Elicitation of suspension cultures of both callus types of C. inophyllum with dried cell powder and culture filtrates of both fungi consistently elicited production of inophyllum A, B, C, and P. In comparison to stem-derived callus, suspension cultures of leaf-derived callus enhanced production of most inophyllum. Of the four inophyllum studied, the highest production of inophyllum A, C, and P was achieved in elicited suspension cultures of leaf-derived callus. Suspension cultures of stem-derived callus enhanced production only of inophyllum B. When suspension cultures of leaf-derived callus were elicited with 40 mg dried cell powder of Phoma spp., a level of 751-fold (6.84 mg/100 g elicited biomass) of inophyllum A was produced, compared to control. Whereas, a level of 414-fold (6.22 mg/100 g elicited biomass) of inophyllum B was produced when suspension cultures of stem-derived callus were elicited with 20 mg dried cell powder of N. sphaerica. When compared to control, a 10% culture filtrate of N. sphaerica in suspension cultures of leaf-derived callus elicited inophyllum C and P production by 928-fold (7.43 mg/100 g elicited biomass) and 750-fold (1.5 mg/100 g elicited biomass), respectively.
Keywords: Biotic elicitation; Calophyllum inophyllum; Endophytic fungi; Inophyllum; Suspension cultures

Genomic determinants of entomopathogenic fungi and their involvement in pathogenesis - Vidhate, Ravindra P.; Dawkar, Vishal V.; Punekar, Sachin A.; Giri, Ashok P. (Microbial Ecology, 2023)
Entomopathogenic fungi offer an effective and eco-friendly alternative to curb insect populations in biocontrol strategy. The evolutionary history of selected entomopathogenic fungi indicates their ancestral relationship with plant endophytes. During this host shifting, entomopathogenic fungi must have acquired multiple mechanisms, including a combination of various biomolecules that make them distinguishable from other fungi. In this review, we focus on understanding various biochemical and molecular mechanisms involved in entomopathogenesis. In particular, we attempt to explain the indispensable role of enlarged gene families of various virulent factors, viz. chitinases, proteases, lipases, specialized metabolites, and cytochrome P450, in entomopathogenesis. Our analysis suggests that entomopathogenic fungi recruit a different set of gene products during the progression of pathogenesis. Knowledge of these bio-molecular interactions between fungi and insect hosts will allow researchers to execute pointed efforts towards the development of improved entomopathogenic fungal strains.
Keywords: Biocontrol; Chitinases; Endophytic fungi; Entomopathogenic fungi; Hydrolytic enzymes; Insect pests

Endophytic entomopathogenic fungi: the next frontier in mycological biocontrol - Patil, Karan S.; Gathalkar, Ganesh B.; Pathan, Ejaj K. (World Journal of Microbiology & Biotechnology, 2026)
Entomopathogenic fungi (EPF) are eco-friendly alternatives to chemical pesticides. However, high costs, the instability of the formulations, sensitivity to environmental factors and variability in virulence limit adoption by farmers. We argue that these problems can be overcome by using EPF strains established as endophytes. The ability of endophytic entomopathogenic fungi (EEPF) to modulate the release of volatiles to attract the predators of insect pests positions them as dual-purpose biocontrol agents in agriculture. As endophytes, these fungi are persistent, lowering the costs for pest control. Endophytic entomopathogenic fungi can also promote plant growth and improve tolerance to abiotic stress. Research on the molecular mechanisms underlying plant tissue colonization by EEPF, their persistence in plants and virulence towards insects suggests that EEPF acquire virulence factors and metabolic versatility through horizontal gene transfer from plants. Therefore, establishing and maintaining EPF as endophytes within plants may compensate for the loss of virulence associated with repeated in vitro subculturing of EPF on artificial media. However, despite these potential advantages of EEPF, challenges still remain, such as variability in endophytic colonization under field conditions, host specificity, ecological risks, and scalability. This review critically evaluates these limitations, focusing on well-studied genera, such as Metarhizium, Beauveria, and Lecanicillium, and outlines future directions for improving the reliability of the application of EEPF. By integrating ecological, molecular, and applied perspectives, we provide a comprehensive and updated framework that positions EEPF as next-generation biocontrol agents in sustainable agriculture.Graphical AbstractEndophytic entomopathogenic fungi protect plants by infecting insect pests and emitting volatiles to attract the natural predators of insect pests. They also promote plant growth by improving the nitrogen fixation and nutrient cycling
Keywords: ; Beauveria; Metarhizium; Biological control; Endophytic fungi; Entomopathogens; horizontal gene transfer; Plant-fungus interactions; Sustainable agriculture